Cell‐derived microparticles contain caspase 3 in vitro and in vivo - ABID HUSSEIN, M. N.; NIEUWLAND, R.; HAU, C. M.; EVERS, L. M.; MEESTERS, E. W.; STURK, A. (Journal of thrombosis and haemostasis, 2005)
Background: Microparticles (MP) from endothelial cells (endothelial microparticles; EMP) circulate in disease states, but the processes such as apoptosis or cell activation underlying their release are unclear. Objectives: We investigated whether adherent (viable) or detached (apoptotic) endothelial cells are the possible source of EMP in vitro, i.e. under control and interleukin (IL)‐1α activation conditions, and in vivo. Methods: Adherent and detached endothelial cells, and EMP, were isolated from human umbilical vein endothelial cell cultures (n = 6), treated without or with IL‐1α (5 ng mL−1; 24 h). Cell fractions were analyzed by flow cytometry for annexin V binding, propidium iodide (PI) and caspase 3 staining (n = 3). Caspase 3 in EMP was studied using Western blot (n = 6) and flow cytometry (n = 6). Plasma from healthy subjects and systemic lupus erythematosus patients (both n = 3) were analyzed for caspase 3‐containing (E)MP. Results: Detached but not adherent cells double‐stained for annexin V and PI, confirming the apoptotic conditions of the detached cells and the viable nature of the adherent cells. Caspase 3 was solely present in the detached cells and procaspase 3 in the adherent cells. Caspase 3 was present in EMP from both control and IL‐1α‐treated cultures. Counts of EMP and detached cells, but not adherent cells, highly correlated (r = 0.959, P < 0.0001). In vivo circulating MP from nucleated (endothelial cells, monocytes) and anucleated cells (platelets, erythrocytes) contained caspase 3. Conclusions: EMP contain caspase 3 and may be mainly derived from detached (apoptotic) endothelial cells in vitro. The presence of caspase 3 in MP from anucleated cell types, however, suggests that its presence may not necessarily be related to apoptosis in vivo but may be associated with caspase 3 activation unrelated to apoptosis.